Colostrum Relationship Between Family Role Whith 0-2 Day Colostrum Giving In Aminah Labor Clinic - Syari Khoniawati; Iis Hanifah; Mega Silvian Natalia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Public knowledge about the importance of breastfeeding is still lacking, especially the provision of colostrum for newborns. Another factor that causes the low coverage of exclusive breastfeeding is the factor of working mothers, culture and family roles. Exclusive breastfeeding is breastfeeding without additional food until the baby is 6 months old. This research is an analytic survey research, while the research design uses a cross sectional survey, which is to measure the behavior of a number of populations through 34 respondents. So that it contains information about the attitudes, beliefs, opinions and behavior of families by giving colostrum. Data were taken by giving questionnaire sheets to patients who gave birth at Aminah's maternity clinic from June to August 2022 with a total population and sample of 34 respondents. Data collection includes coding, editing, scoring, tabulating and entering, then the data is analyzed manually and computer with chi-square test. The results of this study showed that the role of the family in giving colostrum 0-2 days at the Aminah Maternity Clinic was obtained a value of p = 0.002 which was smaller than alpha (0.05), then Ho was rejected H1 was accepted with a coefficient value of 0.513. The conclusion of this study is that there is a significant relationship between the role of the family with the provision of colostrum 0-2 days in the maternity clinic Aminah. And there needs to be an explanation of health workers about the importance of giving colostrum to newborns.